The Influence of Organizational Culture and Employee Involvement on Employee Loyalty in the Quality Manufacturing Division at PT Adis Dimension Footwear, Tangerang Regency - Hasanah, Neneng; Yulandari, Sri; Putri, Narti Eka (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to determine the effect of organizational culture and employee involvement on employee loyalty in the Quality Manufacturing division at PT Adis Dimension Footwear, Tangerang Regency. This study uses a quantitative descriptive method. The population in this study were all employees in the Quality Manufacturing division at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 80 respondents. The results of this study indicate that partially and simultaneously, organizational culture and employee involvement significantly influence employee loyalty in the Quality Manufacturing division at PT Adis Dimension Footwear, Tangerang Regency. This finding indicates that organizational culture and employee involvement can reduce employee loyalty to the company if not managed properly by the company.